Assessing the performance of virtual teams with intelligent agents - Nunes, M.; O'Neill, H. (Virtual and Networked Organizations, Emergent Technologies and Tools. ViNOrg 2011. Communications in Computer and Information Science, 2012)
This study explores the application of intelligent agent technology to the assessment of the performance of virtual teams. From the followed methodology it was possible to 1) create a formal model of agent-mediated team performance, the aTeam model, 2) develop and validate a platform for carrying out experiments, the Promus agent system, 3) use that platform in a test case, the Promus Beer Game experiment, and 4) evaluate these outcomes by running the experiment on user trials. Results show that the intelligent agents are able to perceive and critically evaluate a virtual team’s performance.